Visual outcome on Fitting Rose-K2 XL lens in a case with Terrien’s marginal degeneration - Mishra, S k; Shrestha, G S; Dhungel, P; Aryal, B (Journal of Chitwan Medical College, 2015)
Terrien’s marginal degeneration is an uncommon disease of the peripheral cornea occurring at any age that results in corneal thinning causing corneal irregular astigmatism. RoseK2 XL lens has an aspheric optical zone and employed in the fitting of irregular corneas for vision and comfort while maintaining corneal health. Rose K2 XL lens was fitted in a 17 year female presented to Contact lens clinic of B.P. Koirala Lions Center for Ophthalmic Studies, Kathmandu having RE Terrien’s marginal degeneration. Her presenting visual acuity was 6/60 in right eye and 6/6 in left eye with best subjective refraction OD: +2.00/-3.00X150 and OS: Plano. Her corneal topography revealed irregular corneal astigmatism as indicated by SimK49.85/41.63@137. RoseK2 XL which is a mini-scleral lens, showed an excellent fitting attaining visual acuity 6/6. RoseK2 XL lens provides not only good visual acuity also confirms comfort in patients with corneal marginal degeneration. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11974